Factors Inhibiting English Speaking Skills among English Department Students at Tadulako University - Firdayanti, Roudhotul; Arid, Muhammad; Zamzam, Fadhilah; Kamaruddin, Abd (Universitas Pahlawan Tuanku Tambusai, 2026)
Speaking is one of the most essential skills in English as a Foreign Language learning; however, many students still experience difficulties in developing this skill. This study aims to identify the factors inhibiting English speaking skills among students of the English Education Study Program at Tadulako University. This research employed a mixed-method approach with a sequential explanatory design. Quantitative data were collected through questionnaires distributed to approximately 50 third-semester students using a Likert scale, while qualitative data were obtained through semi-structured interviews with six selected participants. The quantitative data were analyzed using descriptive statistics, and the qualitative data were analyzed using thematic analysis. The findings revealed that students’ speaking difficulties are influenced by both linguistic and psychological factors. Vocabulary limitation was identified as the most dominant factor. In addition, psychological factors such as anxiety and fear of making mistakes reduced students’ confidence and willingness to speak. In contrast, environmental factors, particularly peer support, were not considered significant barriers but rather facilitated speaking development. In conclusion, speaking difficulties result from the interaction of multiple factors; therefore, improving speaking skills requires an integrated approach that enhances vocabulary mastery, increases practice opportunities, and fosters a supportive learning environment.